Synthesis and Insecticidal Activity of Mesoionic Pyrido[1,2-α]pyrimidinone Derivatives Containing a Neonicotinoid Moiety - Pan, Jianke (Molecules, 2018)
Mesoionic pyrido[1,2-α]pyrimidinone derivatives containing a neonicotinoid moiety were designed, synthesized, and evaluated for their insecticidal activity. Some of the title compounds showed remarkable insecticidal properties against Aphis craccivora. Compound I13 exhibited satisfactory insecticidal activity against A. craccivora. Meanwhile, label-free proteomics analysis of compound I13 treatment identified a total of 821 proteins. Of these, 35 proteins were up-regulated, whereas 108 proteins were down-regulated. Differential expressions of these proteins reflected a change in cellular structure and metabolism.